Discovery of Novel Myristic Acid Derivatives as N-Myristoyltransferase Inhibitors: Design, Synthesis, Analysis, Computational Studies and Antifungal Activity - Saleem Javid; Hissana Ather; Umme Hani; Ayesha Siddiqua; Shaik Mohammad Asif Ansari; Dhivya Shanmugarajan; Honnavalli Yogish Kumar; Rajaguru Arivuselvam; Madhusudan N. Purohit; B. R. Prashantha Kumar (MDPI AG, 2023)
In recent years, N-Myristoyltransferase (NMT) has been identified as a new target for the treatment of fungal infections. It is observed that at present, there are increased rates of morbidity and mortality due to fungal infections. Hence, a series of novel myristic acid derivatives were designed via molecular docking studies and ADMET studies by targeting NMT (N-Myristoyltransferase). The designed myristic acid derivatives were synthesized by converting myristic acid into myristoyl chloride and coupling it with aryl amines to yield corresponding myristic acid derivatives. The compounds were purified and characterized via FTIR, NMR and HRMS spectral analyses. In this study, we carried out a target NMT inhibition assay. In the NMT screening assay results, the compounds 3u, 3m and 3t showed better inhibition compared to the other myristic acid derivatives. In an in vitro antifungal evaluation, the myristic acid derivatives were assessed against Candida albicans and Aspergillus niger strains by determining their minimal inhibitory concentrations (MIC50). The compounds 3u, 3k, 3r and 3t displayed superior antifungal capabilities against Candida albicans, and the compounds 3u, 3m and 3r displayed superior antifungal capabilities against Aspergillus niger compared to the standard drug FLZ (fluconazole). Altogether, we identified a new series of antifungal agents.